Bone marrow transplantation in the treatment of alpha-mannosidosis. Issue 10 (October 1987) - Will, A; Cooper, A; Hatton, C; Sardharwalla, I B; Evans, D I; Stevens, R F
Abstract : Bone marrow transplantation was performed in a patient with alpha-mannosidosis. To our knowledge this is the first time such treatment has been attempted. The patient died 18 weeks after successful grafting and specimens of tissues were obtained at necropsy. Alpha-mannosidase activity in spleen and liver was just below normal (spleen 102 mumol/g/hour, control 113-330; liver 29 mumol/g/hour, control 30-131). Splenic alpha-mannosidase activity was indistinguishable from the control enzyme with respect to the Michaelis constant, heat stability, and inhibition by cobalt ions, as was 86% of the liver enzyme. In brain tissue alpha-mannosidase activity was 7% of controls, and less than one third had the properties of the normal enzyme. Oligosaccharides were present only in small amounts in liver and spleen, whereas they were greatly increased in brain tissue. Electron microscopic pictures of liver and spleen tissue showed normal morphology, but brain tissue showed definite vacuolation. These findings suggest that transplantation reversed the somatic changes of alpha-mannosidosis but did not affect lysosomal storage within brain tissue. It is concluded that marrow transplantation may not be a suitable treatment for alpha-mannosidosis.